Student Question

`f(x)=4/(3x+2) , c=3` Find a power series for the function, centered at c and determine the interval of convergence.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

To determine the power series centered at c, we may apply the formula for Taylor series:

`f(x) = sum_(n=0)^oo (f^n(c))/(n!) (x-c)^n`


`f(x) =f(c)+f'(c)(x-c) +(f''(c))/(2!)(x-c)^2 +(f^3(c))/(3!)(x-c)^3 +(f'^4(c))/(4!)(x-c)^4 +...`

To list the `f^n(x)` for the given function `f(x)=4/(3x+2)` centered at `c=2` , we may apply Law of Exponent: `1/x^n = x^-n`  and  Power rule for derivative: `d/(dx) x^n= n *x^(n-1)` .

`f(x) =4/(3x+2)`

     ` =4(3x+2)^(-1)`

Let `u =3x+2` then `(du)/(dx) = 3` .

`d/(dx) c*(3x+2)^n = c *d/(dx) (3x+2)^n`

                            `= c *(n* (3x+2)^(n-1)*3`

                            ` = 3cn(3x+2)^(n-1)`

`f'(x) =d/(dx) 4(3x+2)^(-1)`

          `=3*4*(-1) *(3x+2)^(-1-1)`

           `=-12(3x+2)^(-2) or 2/(3x+2)^2`

`f^2(x) =d/(dx) -12(3x+2)^(-2)`


          `=72(3x+2)^(-3) or 72/(3x+2)^3`

`f^3(x) =d/(dx) 72(3x+2)^(-3)`


           `=-648(3x+2)^(-4) or -648/(3x+2)^4`

Plug-in `x=3` for each `f^n(x)` , we get:


        `=4/ 11`



          `= -12/121`

`f^2(3)=72/(3(3)+2)^3 `



`f^3(3)=-648/(3(3)+2)^4 `


           `= -648/14641`

Plug-in the values on the formula for Taylor series, we get:

`4/(3x+2)= sum_(n=0)^oo (f^n(3))/(n!) (x-3)^n`

` = sum_(n=0)^oo (f^n(3))/(n!) (x-3)^n`

` =4/11+(-12/121)(x-3) +(72/1331)/(2!)(x-3)^2 +(-648/14641)/(3!)(x-3)^3 +...`

` =4/11-(12/121)(x-3) +(72/1331)/2(x-3)^2 - (648/14641)/6(x-3)^3 +...`

` =4/11-12/121(x-3) +36/1331(x-3)^2 -108/14641(x-3)^3 +...`

` = sum_(n=1)^oo 4(-3(x-3))^(n-1)/11^n`

` = sum_(n=1)^oo 4(-3(x-3))^(-1)(-3(x-3))^n/11^n`

` = sum_(n=1)^oo 4/(-3(x-3))((-3(x-3))/11)^n`

` =sum_(n=1)^oo 4/(-3x+9)((-3(x-3))/11)^n`

To determine the interval of convergence, we may apply geometric series test wherein the series `sum_(n=0)^oo a*r^n`  is convergent if `|r|lt1 or -1 ltrlt 1` . If `|r|gt=1` then the geometric series diverges.

By comparing  `sum_(n=1)^oo 4/(-3x+9)((-3(x-3))/11)^n` with `sum_(n=0)^oo a*r^n` , we determine: `r = (-3(x-3))/11` .

Apply the condition for convergence of geometric series: `|r|lt1` .







Multiply each sides by `11` :



Add 9 on each sides:



Divide each side by `3` :


`-2/3ltxlt20/3 `

Thus, the power series  of the function `f(x) =4/(3x+2)` centered at `c=3` is `sum_(n=1)^oo 4/(-3x+9)((-3(x-3))/11)^n`

 with an interval of convergence: `-2/3ltxlt20/3` .

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial